1989
DOI: 10.1080/18811248.1989.9734367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Wave Initiation and Slugging of Air-Water Stratified Flow in Horizontal Duct

Abstract: Two-phase air-water flow was studied experimentally under atmospheric conditions Wave growth and slugging from stratified flow regime in a horizontal duct were analyzed by using a video camera. The result for slug initiation was compared with the instability criteria based on linear analysis and the empirical correlations of other researchers. The required instability criteria is in good agreement. The reason for the necessary lower gas velocity in comparison with Kelvin-Helmholtz relation and growth of short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In general, a stratified flow is observed in this downward pipe, in accordance with a flow regime map of Spedding and Nguyen [35] and a similar experimental setup of Vieiro et al [30]. This stratified flow promotes the occurrence of hydrodynamic slug flow driven by the gas-liquid interface instabilities typically taken as conditions for the slug initiation in the experiments [36,37] and numerical simulations [38,39].…”
Section: Experimental Backgroundsupporting
confidence: 86%
“…In general, a stratified flow is observed in this downward pipe, in accordance with a flow regime map of Spedding and Nguyen [35] and a similar experimental setup of Vieiro et al [30]. This stratified flow promotes the occurrence of hydrodynamic slug flow driven by the gas-liquid interface instabilities typically taken as conditions for the slug initiation in the experiments [36,37] and numerical simulations [38,39].…”
Section: Experimental Backgroundsupporting
confidence: 86%
“…Instabilities can appear and evolve along such interfaces [4,5]. For example, the Kelvin-Helmholtz instability develops along a sheared interface, and grows at a distinct wavelength that has been predicted theoretically [6,7], and confirmed experimentally [8]. Kelvin-Helmholtz instabilities can appear for example on a surface of water below a flow of air [5,9].…”
Section: Introductionmentioning
confidence: 58%
“…Ansari and Nariai [9] developed an experimental facility to analyse the wave growth and onset of slugging. They concluded that before slug formation, another wave mechanism happens that includes a few waves with short wavelengths.…”
Section: Introductionmentioning
confidence: 99%